Anthropometry and body composition of youth females aged 13-17 years old - Cândido Simões Pires Neto; Ciro Romelio Rodriguez-Añez; Ronaldo Domingues Filardo (Universidade Federal de Santa Catarina, 2000)
The objective of the this study was to analyze and compare anthropometric and body composition index of young females aged 13-17 years old with the studies of Slaughter et al. (1984), Meleski et al. (1982), Thorland et al. (1983 e 1984) and Gaya et al. (1997). For such, were measured the anthorpometric variables height (EST), weight (MC), 4 skinfolds (DC), 3 bone diameters (DO) and 2 circumferences (PER), beside the age. The sample were 50 young female (age x =15,8±0,9 years; height x =167,07±6,2 cm and e weight x = 57,97±7kg), being 27 volleyball player and 23 basketball players. To stimate corporal density (D) the equation proposed by Thorland et al (1984) was used and the fat percent (%G) was obtained by the Lohman (1986) equation. The %G of the other studies was recalculated by the Lohman (1986) equation for comparison with this study. To analyze the data the descriptive statistics was used, beside the "t" test of student for independent group and "t" test for one mean (p<0,05). When compared the group by sport can be observed that they do not differ, exception for the wrist. When compared the variables with the other studies were observed differences for all the skinfolds, circumferences and %G. Can be seen also that the Brozek (1963) equation, overestimated the %G, provably because the chemical immaturity of the subjects. Can be concluded that: 1) the Brozek et al. (1963) equation must be avoid in adolescents; 2) the similarity of age between the compared groups was not enough to avoid the differences in the anthropometric and body composition variables, 3) The groups of this study (volleyball and basketball) do not differ for the analyzed variables, except for the writs diameter, probably it is a characteristic of volleyball players were can be seen a large diameter. RESUMO O objetivo deste estudo foi comparar e analisar indicadores antropométricos e de composição corporal de jovens do sexo feminino entre 13 e 17 anos, com os estudos de Slaughter et al. (1984), Meleski et al. (1982), Thorland et al. (1983 e 1984), Gaya et al. (1997). Para tal, foram mensuradas as variáveis antropométricas estatura (EST), massa corporal (MC), 4 dobras cutâneas (DC), 3 diâmetros ósseos (DO) e 2 perímetros (PER), além do registro da idade. A amostra esteve constituída de 50 jovens (idade x =15,8±0,9 anos; estatura x =167,07±6,2 cm e MC x =57,97±7kg), sendo 27 jogadoras de voleibol e 23 jogadoras de basquetebol. A estimativa da densidade corporal (D) foi realizada utilizando a equação proposta por Thorland et al. (1984) e a gordura relativa (%G) foi obtida pela equação de Lohman (1986). Os percentuais de gordura dos outros estudos foram recalculados pela equação de Lohman (1986) para comparação com o presente estudo. Para a análise dos dados utilizou-se a estatística descritiva e o teste "t" de student para grupos independentes além do teste "t" para uma média (p<0,05). Quando comparados os grupos por esporte, pode-se observar que não diferem estatisticamente com exceção do diâmetro rádio-ulnar. Quando comparadas as variáveis com os outros estudos, observam-se diferenças em todas as dobras cutâneas, perímetros e %G em relação aos grupos analisados. Pode-se observar também que a equação de Brozek (1963), superestima o %G, provavelmente devido à imaturidade química dos sujeitos. Conclui-se que: 1) deve-se evitar a utilização da equação de Brozek et al. (1963) em adolescentes; 2) a semelhança da idade entre os grupos comparados não impediu que houvesse diferenças significativas nas variáveis antropométricas e de composição corporal e, 3) os grupos do presente estudo (voleibol e basquetebol) não diferem estatisticamente entre si nas variáveis analisadas, com exceção do diâmetro rádio-ulnar, provavelmente uma característica do voleibol onde se observa diâmetro maior.